(untitled) (Вестник КазНУ. Серия Экономическая, 2016)
The paper discusses the ways of solving the current problems in the area of environmental protection, particularly in the oil and gas sector of Kazakhstan by the environmental audit. Today, the environmental audit is one of the most important areas of the audit. The environmental audit can solve problems that could affect the improvement of environmental quality in the field of oil and gas. Environmental problems are reflected in the deterioration of the Caspian Sea, which has a negative impact on flora and fauna of the region. Despite the existence of legislative norms of environmental audit, taking over the foreign experience can improve the system of environmental management. Environmental audit is able to adjust and improve environmental inspections at the enterprises of oil and gas, which in its turn will lead the improving of the environment in general.